1988
DOI: 10.1007/bf01871397
|View full text |Cite
|
Sign up to set email alerts
|

Inward rectifier K channels in renal epithelioid cells (MDCK) activated by serotonin

Abstract: The present study has been performed to test for the effect of intracellular calcium and of serotonin on the channel activity in patches from subconfluent MDCK-cells. In inside-out patches, inwardly rectifying potassium-selective channels are observed with open probabilities of 0.01 +/- 0.01, 0.24 +/- 0.03 and 0.39 +/- 0.07, at 100 nmol/liter, 1 mumol/liter or 10 mumol/liter calcium activity, respectively. The single-channel slope conductance is 34 +/- 2 pS, if the potential difference across the patch (Vp) is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

1990
1990
1996
1996

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…The open probability of the channel was on average 0.62 at Vp = 0 and increased with depolarization, but the extent of the voltage dependence was quite variable among experiments. These characteristics are common to K channels found in several epithelial preparations, such as basolateral membranes of turtle colon (Richards and Dawson, 1986), rabbit proximal convoluted (Parent et al, 1988) and straight renal tubules , dogfish rectal gland (Greger, Gogelein, and Schlatter, 1987a), subconfluent MDCK cells (Friedrich, Paulmichl, Kolb, and Lang, 1988;Friedrich et al, 1989), and apical membranes of thick ascending limb of rat kidney (Bleich, Schlatter, and Greger, 1990;Greger, Bleich, and Schlatter, 1990). All these channels exhibit inward rectification, conductances in the range 50--70 pS with high K on both sides of the patch, and, where analyzed, an open time constant of ~ 10 ms, at least two closed time constants, the smaller ~ 1 ms, and a weak increase of the open probability with depolarization.…”
Section: K Currentsmentioning
confidence: 64%
“…The open probability of the channel was on average 0.62 at Vp = 0 and increased with depolarization, but the extent of the voltage dependence was quite variable among experiments. These characteristics are common to K channels found in several epithelial preparations, such as basolateral membranes of turtle colon (Richards and Dawson, 1986), rabbit proximal convoluted (Parent et al, 1988) and straight renal tubules , dogfish rectal gland (Greger, Gogelein, and Schlatter, 1987a), subconfluent MDCK cells (Friedrich, Paulmichl, Kolb, and Lang, 1988;Friedrich et al, 1989), and apical membranes of thick ascending limb of rat kidney (Bleich, Schlatter, and Greger, 1990;Greger, Bleich, and Schlatter, 1990). All these channels exhibit inward rectification, conductances in the range 50--70 pS with high K on both sides of the patch, and, where analyzed, an open time constant of ~ 10 ms, at least two closed time constants, the smaller ~ 1 ms, and a weak increase of the open probability with depolarization.…”
Section: K Currentsmentioning
confidence: 64%
“…The Ca"2-sensitive K+ channel has to be activated by agonists such as serotonin or minoxidil sulfate which exert their effect via the PKC signalling pathway ( 12,13 were found. Moreover, in ras fibroblasts pretreated with lithium, elevated levels of 1,4,5-inositol-triphosphate were found and bradykinin also caused oscillations of the cell membrane potential.…”
Section: Discussionmentioning
confidence: 99%
“…Microelectrode studies suggested a Ca" -activated K+ channel (6). Such a channel has been described in nontransformed MDCK cells, too, and its regulation has been studied extensively (12,13). Furthermore, it is known that ras-transformation of fibroblasts leads to the expression of a novel Ca2+-activated K+ current (14).…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence, however, that 5-HT, in the kidney, can exert marked effects, namely at the level of vasculature and glomerular and tubular structures. The subtypes of 5-HT receptors identified in the kidney and renal cell lines include the 5-HT2 subtype in renal blood vessels (Janssens & Van Nueten, 1986;Wright & Angus, 1987;Shoji et al, 1989;Blackshear et al, 1991) and the glomerulus (Hamamori et al, 1988;Takuwa et al, 1989), the 5-HTlA subtype in the medullary and cortical tick ascending limb of Henle and distal convoluted tubules (Raymond et al, 1993), the 5-HTlB subtype in OK cells from the opossum kidney (Murphy & Bylund, 1990) and the 5-HTID in MDCK cells from the canine kidney (Frederich et al, 1988). In a recent study in the rat kidney, Ramond et al (1993), employing an immunohistochemical technique, failed to identify the 5-HTlA receptor subtype in the proximal nephron.…”
Section: Statisticsmentioning
confidence: 99%